(untitled) (Revista INTEREDU11, 2024)
In this article we present a bibliographic essay of the report: Reimagining our futures together: a new social contract for education published in 2022 by UNESCO. This continues the tradition of this agency of producing prospective reports on education from a global perspective. Through a process of analysis, chapters three, four and five are specifically assessed. These, focus on the need for cooperative and solidarity-based pedagogies, common knowledge, curricula and the transformative work of teachers, respectively. The text highlights the urgency of implementing a new social contract that allows knowledge and learning to shape the future destiny of humanity and the planet. This purpose demands the recognition of education as a public good and as a political project built with the equitable participation of all people.